Analisis Problem Solving Matematis Menurut Teori Krulik-Rudnick Siswa Sekolah Dasar Kelas V - Arinda Dwi Agustin; Maeva Juliana Ningtyas; Milla Berlian Amanda; Berlian Puspa Devitasari; Dewi Febrianti; Rissa Prima Kurniawati (Prosiding Konferensi Ilmiah Dasar, 2026)
This study analyzed the mathematical problem-solving abilities of fifth grade elementary school students in solving HOTS based word problems according to the five stages of the Krulik-Rudnick model. Using a qualitative descriptive approach, the study involved five students from SDN Rejomulyo 01 who were selected through purposive sampling data were collected through tests and documentation and validated through triangulation. The results show that all participants mastered the read and think and select a strategy stages well four participants mastered the explore and plan and find an answer stages, although one participant incorrectly wrote the unit of measurement for the answer; meanwhile, the reflect and extend stage was the weakest, as only two participants were able to verify their answers. It can be concluded that the students are already proficient in understanding problems and selecting strategies, but their ability to reflect on and develop their answers still needs improvement.